Funktioniert fairer Handel? Ökonomische Überlegungen zum alternativen Handel mit Kaffee - Torsten Steinrücken (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2003)
In the last more and more consumers evince increasing interest in fair traded products. This trade concept is designed to help mainly producers of agricultural products to keep some basic social producing criteria. The different Fair-Trade-Organisations try to implement better work- and life conditions in the developing countries by announcing those producers fixed prices for the current products. The fixed price is considered to be just and acceptable since it does not exloit producers social weakness. It is perceptibly higher than the price at the world market. A part of all consumers pay the higher price and support in that way the efforts of the Fair-Trade-Organisations. The present article discusses the economics of the fair trade instrument and the degree of achievement of the target objectives. The mechanism of the fair-trade-concept is illustrated considering the example of trade with coffee, because coffee stands for the major share of all fair traded products.
Keywords: F10; L15; L66; Q17; 330; Fair Trade; Coffee Market